Analisis Preferensi Konsumen Terhadap Pembelian Buah Melon di Surakarta - Suhita, Cahyaningtyas Putri; Mei Tri Sundari; Sugiharti Mulya Handayani; Desy Setyaningrum (MES Bogor, 2025)
Melon, especially the Cucumis melo species, is a fruit that is widely favored by the public for various reasons, ranging from its sensory appeal to its nutritional benefits. Melon has various characteristics including variations in shape, fruit weight, net skin lines, skin color, fruit color, flesh texture, water content, aroma, and price. The many variations in attributes in melons that influence consumer preferences for purchasing this melon are the basis for the importance of this study. The total number of respondents in this study was 80 respondents. This study is a study of consumer preferences for purchasing melons in Surakarta. The attributes analyzed in this study are: taste, weight, aroma, fruit texture, fruit color, water content, shape, net skin lines, and price. The data analysis method was carried out by validity testing, reliability testing, analysis using the chi-square method. The results showed that all attributes in this study were said to be significant for consumer preferences for purchasing melons. The sweet taste of melon is the most important attribute in purchasing melons. The fragrant and refreshing aroma typical of melons and the bright orange color of the flesh, and the crunchy texture of the fruit are three important attributes in purchasing melons. Meanwhile, high water content, round fruit shape, weight 1-1.5kg are attributes with a ranking of five to seven in purchasing melons. Net skin lines and melon price are the last attributes, meaning that both attributes are the last considerations in purchasing melons.